2019
DOI: 10.4149/neo_2018_180328n209
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of functional tumor burden on 68Ga-DOTATOC PET/CT in patients with pancreatic neuro-endocrine tumors

Abstract: Despite their relative quiescence, pancreatic neuro-endocrine tumors (pNET) can correspond to various presentations and outcomes. Several prognostic factors have been identified, including maximal standardized uptake value of the most intense focus (maxSUVmax) on Positron Emission Tomography (PET) with a somatostatin analogue. Herein, we investigate the prognostic value on progression free-survival of the total functional tumor volume (TFTV) measured by 68 Ga-DOTATOC PET. From patients who underwent 68 Ga-DOTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…We therefore employed a standardized patient-specific cutoff to delineated lesions based on the method described for 18 F-FDG (19). Recently, a number of papers have described the prognostic implications of tumor volume derived from 68 Ga-DOTATATE (10-12) or 68 Ga-DOTATOC (13,14), but not for 64 Cu-DOTATATE. In order to obtain tumor volume, different strategies were utilized; manual delineation of lesions including areas with either 41% or 50% of lesion SUVmax or semi-automatic delineation with individual SUVmax threshold based on agreement between anatomical and functional lesion delineation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore employed a standardized patient-specific cutoff to delineated lesions based on the method described for 18 F-FDG (19). Recently, a number of papers have described the prognostic implications of tumor volume derived from 68 Ga-DOTATATE (10-12) or 68 Ga-DOTATOC (13,14), but not for 64 Cu-DOTATATE. In order to obtain tumor volume, different strategies were utilized; manual delineation of lesions including areas with either 41% or 50% of lesion SUVmax or semi-automatic delineation with individual SUVmax threshold based on agreement between anatomical and functional lesion delineation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain tumor volume, different strategies were utilized; manual delineation of lesions including areas with either 41% or 50% of lesion SUVmax or semi-automatic delineation with individual SUVmax threshold based on agreement between anatomical and functional lesion delineation. However, none of the studies reported time spent on segmentation of tumors (8)(9)(10)(11)(12)(13)(14). In the present study, the time spent was approximately 20 minutes per patient, although less time (down to 5 minutes) was needed when areas of physiological uptake (kidney, urinary bladder and spleen) could be avoided due to tumor location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of eight studies involving 593 patients were included in our meta-analysis. Five studies (21,22,(28)(29)(30) were retrospective and three studies (31)(32)(33) were a prospective design. According to the WHO grade, three researches (22,29,30) included well-differentiated NETs (grade 1 and/or 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…While high correlation found between Ki and TBR indicated that the latter might be more accurate metrics than SUV for semi-quantitative assessment of [ 68 Ga]Ga-SST lesion uptake and treatment response monitoring [101]. Total functional tumor volume (TFTV) measured on [ 68 Ga]Ga-SST PET and computed by summing the volumes of all pathological foci was suggested as prognostic biomarker with cut-off of 13.8 cm 3 [102]. Somatostatin receptor expressing tumor volume (SRETV), defined as tumor volume with higher [ 68 Ga]Ga-SST uptake than 50% of SUV max within the volume of interest for each lesion, demonstrated prognostic value of survival [103].…”
Section: Impact Of Sst Radiopharmaceuticals On Patient Treatment Manamentioning
confidence: 99%